Penundukan Diri Non-Muslim dalam Qanun Jinayat Aceh: Penyimpangan atau Pengembangan Asas Hukum Pidana? - Mohd. Din; Ali Abubakar; Marah Halim (Jurnal Penelitian Hukum De Jure, 2023)
This article aims to provide legal logic for the permissibility of choosing criminal law for non-Muslims who commit criminal acts regulated in the Aceh Qanun Jinayat based on one of the legal principles raised (endorsement) as the basis for establishing norms in the qanun in question, namely the principle of submission which is actually not recognized in criminal law. The research data are several decisions of the Syar’iyah Court in Aceh against violations of the Qanun Jinayat committed by non-Muslims. It is assumed that the decisionis a shift in the principles of criminal law. This problem will be analyzed by observing the basic principles of criminal law, including the principles of the application of criminal law and the politics of criminal law. The results of the study showed that from the point of view of the principles of criminal law which is a compelling law, this submission is a deviation, but from a legal-political perspective, because the birth of permissible provisions in qanuns is a political process, where the demand to apply Islamic Sharia which basically only applies to Muslims, then as a softening of the territorial principle non-Muslims are allowed to vote.